A Library Story: Building a New Central Library - Vogel, Jennifer (Millbrook Press, 2012)
The city of Minneapolis, in the state of Minnesota, has a long library history. Its first public library was built in 1889 and the castle like building not only housed books but it also had a small collection of live animals, and a pair of real Egyptian mummies. This library finally got too small for the book collection and in 1961 the books (and the two mummies) were moved to a bigger and more modern building. In addition to its books this library had a planetarium, which delighted thousands of children and adults. In 2000 it was decided that the Minnepolis Public Library needed a new home. Once again the book collection was getting too big for the building, and the library did not have the space to house movies, magazines, and the many other things that the library wanted to have for its patrons. And so the people of Minneapolis set about raising the money needed for the new library. It was not an easy thing to do but their love of books encouraged the Minnesotans to dig deep into their pockets to pay for the new building. Once this was done it was then time to set about designing the new building. Architect Cesar Pelli was given the job of creating a building that would fit in with the surrounding buildings, and one that would ""be able to change as the library's needs changed."" His final design set a whole new standard for library architecture. The new library would not only have more room for books than ever before but it would also have a caf